Етапи еволюції від ранніх Homo до людини сучасного фізичного типу: науковий огляд - Ніколіна, Інна; Очеретяний, Володимир (Naukovì zapiski. Serìâ: Ìstorìâ (Vìnnicʹkij deržavnij pedagogìčnij unìversitet ìmenì Mihajla Kocûbinsʹkogo), 2023)
The purpose of the article is an attempt to conduct a comparative analysis of the morphological features of Homo habilis and Homo erectus, their local variations, to study the essence of the «Neanderthal problem» and to study the problem of continuity between Homo neanderthalensis and Homo sapiens sapiens. The research methodology is based on the use of general scientific principles: scientific objectivity, historicism, a systematic approach in the analysis of historical processes considered in this article. Such special historical methods as descriptive, problem-chronological, historical-systemic, comparative-historical have proven to be effective. The scientific novelty of the research is determined by the fact that using the achievements of foreign and domestic scientists and the assets of paleoanthropology and genetics, the authors offer their own perspective on the evolution of humanity. Conclusions. Africa turned out to be a key place in the evolutionary process of human beings, because the most evidence of the existence of ancient forms of Homo and their possible ancestors was discovered there. Australopithecus, representatives of anthropoids, were still close to primates because of their brain structure but at the same time the diversity of Australopithecus was large and included quite advanced individuals. Homo habilis became the first human beings who were able to make tools and this fact indicates their ability to use the improved hand effectively. Homo erectus and all their local variants-offshoots on other continents are the undoubted representatives of the genus Homo. The brain of these species has a greater intellectual similarity to the modern human beings than the brain of Homo habilis despite the preservation of features of primates in their morphology. Neanderthals became the first human beings exclusively European species in the context of their geographical distribution on Earth. The linear model of evolution «Homo Neanderthalensis – Homo Sapiens sapiens» was disproved because of the application of modern paleogenetic methods and many reasons for the mass extinction of their population were named in the last two decades. Метою статті є спроба проведення порівняльного аналізу морфологічних ознак Homo habilis і Homo erectus, їх місцевих варіацій, дослідження сутності «неандертальської проблеми» і вивчення проблеми наступності між Homo neanderthalensis і Homo sapiens sapiens. Методологія дослідження ґрунтується на використанні загальнонаукових принципів: наукової об’єктивності, історизму, системного підходу, в аналізі історичних процесів, що розглядаються в зазначеній статті. Ефективними виявилися такі спеціальні історичні методи, як описовий, проблемно-хронологічний, історико-системний, порівняльно-історичний. Наукова новизна дослідження визначається тим, що використовуючи здобутки зарубіжних і вітчизняних науковців та надбання палеоантропології, генетики, автори пропонують власний погляд на еволюцію людства. Висновки. Африка виявилась ключовим місцем еволюційного процесу людини, адже тут було виявлено найбільше доказів існування давніх форм Homo та їх можливих предків. Австралопітеки як представники антропоїдів, які за мозковою будовою були ще близькими до приматів, але в той же час різноманіття австралопітеків було великим, що включало в себе і доволі прогресивні особини. Homo habilis стали першими, хто виготовляв знаряддя праці, що свідчить про їх вміння ефективно використовувати вдосконалену кисть руки. Безсумнівним представником роду Homo є Homo erectus з усіма його місцевими варіантами – відгалуженнями на інших континентах. Незважаючи на збереження ознак приматів у їх морфології, мозок цього виду вже має більшу схожість в інтелектуальному відношенні до сучасної людини, ніж мозок Homo habilis. Неандертальці стали першим виключно європейським видом в контексті їх географічного поширення на Землі. В останні два десятиліття спростовано лінійну модель еволюції «Homo neanderthalensis – Homo sapiens sapiens» завдяки застосуванню сучасних палеогенетичних методів та названо безліч причин масового вимирання їх популяції.